Fixed-Point Theorems in Metric and 2-Metric Spaces: A Comparative Study - Hyseni, Blerta (Journal of Research in Vocational Education, 2025)
We present the concept of compatibility for a pair of self-maps on a 2-metric space. We also give fixed point theorems for pairs and quadruples of self-maps on a 2-metric space that meet specific generalized contraction criteria. Versions of the same have also been obtained in metric space.